Drivers of Social Media Use in Disaster Management and Impact on User Satisfaction: The Role of Psychological Conditions and Information Accessibility - Jeremie Katembo KAVOTA; Daniel TOMIUK; Manish VERMA (Communications of International Proceedings, 2023)
The aim of this study is to determine social factors behind social media use and the impact of their use on psychological conditions and satisfaction in disaster management context.  In the management of disasters field, social drivers of social media use are not yet well clarified et explained in literature. Also, little is known as to whether social media usage contributes positively to stakeholders’ psychological well-being and whether that reflects positively on user satisfaction. In this paper, we propose an empirical study that can help fill this gap. Our research model combines elements of social support theory, diffusion of innovation, institutional theory, and Kahn’s theoretical model of psychological conditions. We present relative advantage, compatibility, interactivity, and institutional pressure as drivers of social media. We propose a mixed-method approach to test our model. An initial quantitative assessment using PLS-SEM will be followed by a qualitative study using interviews to help clarify/enrich our understanding of the results and the interrelationships between key variables.  Findings of this study are expected to underline social drivers of social media in management of disasters context. Furthermore, results will highlight whether social media use impacts positively on users’ satisfaction depends on whether these platforms promote psychological conditions helping victims to better deal/cope with disasters. Finally, whether social media usage promotes beneficial psychological conditions will depend on whether the right kind of information/support is accessible when needed.
Keywords: : social media use; disaster management; information accessibility; psychological conditions; satisfaction